The public university, religion, and a pluralist platform for communication - S. A. de Freitas (Acta Theologica)
This article endeavours the optimalisation of the discussion on “religion, faith and the public university” by arguing for a pluralist platform for communication. Although reference to the “public” university is essential for a proper understanding of such a platform, there are concerns regarding such a concept. It is also explained how the question about the purpose of higher education is inextricably linked to discussion on the promotion of pluralist platforms for communication in the context of “religion, faith and the public university”. Although efforts at seeking a common language in public fora are important, it is also important to try to include differing communicative forms that are especially relevant when discussing the purpose of (higher) education. It is concluded that aiming towards a pluralist platform for communication when discussing “religion, faith and the public university” is most suited towards efforts directed at the materialisation of a truly accommodative society